Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning di Kelas IV Sekolah Dasar - Siti Julaiha Kurniati; Taufina Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research aims to describe the improvement of integrated thematic learning processes by using the Discovery Learning model in Class IV SD Negeri 09 Bandar Buat Kota Padang. This type of research is PTK with qualitative and quantitative approaches. The study was conducted in two cycles. Research data in the form of observations and tests. Subjects in this research were teachers and students of class IV. The results of the first cycle study RPP 76.56% (C), second cycle 93.75% (SB). The implementation of aspects of teacher learning in the first cycle 81.26% (B), second cycle 90.6% (SB). Aspects of students in the first cycle were 81.26% (B), the second cycle was 90.6% (SB). Student learning outcomes cycle I 66.5, cycle II to 87. It can be concluded in research that the Discovery Learning model can improve the integrated thematic learning process.